2021
DOI: 10.3390/cancers13194959
|View full text |Cite
|
Sign up to set email alerts
|

Superior Overall Survival in Patients with Colorectal Cancer, Regular Aspirin Use, and Combined Wild-Type PIK3CA and KRAS-Mutated Tumors

Abstract: The impact of aspirin use after the diagnosis of colorectal cancer is unknown. Among others, PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha) mutational status was proposed as a molecular biomarker for the response to adjuvant aspirin therapy. However, prognostic data on aspirin use after a colorectal cancer diagnosis in relation to KRAS mutational status is limited. In a single-center retrospective study, we obtained KRAS and PIK3CA mutational status in a cohort of 153 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The first group includes primary genes controlled directly by aspirin, i.e., PTGS2 and PTGES2 . The second group consists of genes involved in cell signaling and cell proliferation like cMyc , EGFR , BCL2 , WNT , KRAS , WNT6 , BRAF , MUC1 , PIK3CA , PARP1 , PARP2 , STAT3 , MAPK , JAK/STAT , and BAX [ 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; the third group includes genes for cytokines or their receptors (e.g., IFNγ , IL1β , IL2 , IL4 , IL5 , IL6 , IL7 , IL8 , IL10 , IL12 (p70) , IL13 , IL17 , CXCR1 , CXCR2 , PTGS2 , PTGES2 , NFKB1 , and TNFα ) [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; and the fourth group consists of tumor suppressor genes including P53 , BRCA1 [ 43 ], hMLH1 , hMSH2 , hMSH6 , and hPMS2 [ 44 , 45 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first group includes primary genes controlled directly by aspirin, i.e., PTGS2 and PTGES2 . The second group consists of genes involved in cell signaling and cell proliferation like cMyc , EGFR , BCL2 , WNT , KRAS , WNT6 , BRAF , MUC1 , PIK3CA , PARP1 , PARP2 , STAT3 , MAPK , JAK/STAT , and BAX [ 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; the third group includes genes for cytokines or their receptors (e.g., IFNγ , IL1β , IL2 , IL4 , IL5 , IL6 , IL7 , IL8 , IL10 , IL12 (p70) , IL13 , IL17 , CXCR1 , CXCR2 , PTGS2 , PTGES2 , NFKB1 , and TNFα ) [ 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; and the fourth group consists of tumor suppressor genes including P53 , BRCA1 [ 43 ], hMLH1 , hMSH2 , hMSH6 , and hPMS2 [ 44 , 45 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that the benefit appears in all cancers and is not limited to any cancer in particular. For example, aspirin use has been associated with improved survival for colorectal cancer (HR = 0.38; 95% CI = 0.17–0.87; p = 0.02) [ 6 ], biliary tract cancer [ 7 , 8 ], breast cancer (adjusted HR = 0.69, 95% CI 0.47–0.98) [ 9 ], prostate cancer (adjusted hazard ratio, 0.43; 95% CI, 0.21 to 0.87; p = 0.02) [ 10 ], and Endometrial cancer (hazard ratio 0.46, 95% CI 0.25–0.86, p = 0.014) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rst group includes primary genes controlled directly by aspirin, i.e., PTGS2 and PTGES2. The second group consists of genes involved in cell signaling and cell proliferation like cMyc, EGFR, BCL2, WNT, KRAS, WNT6, BRAF, MUC1, PIK3CA, PARP1, PARP2, STAT3, MAPK, JAK/STAT, BAX 6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] ; the third group, genes for cytokines or their receptors (e.g., IFNγ, IL1β, IL2, IL4, IL5, IL6, IL7, IL8, IL10, IL12 (p70), IL13, IL17, CXCR1, CXCR2, PTGS2, PTGES2, NFKB1, and TNFα); 30,[33][34][35][36][37][38][39][40][41][42] and the fourth group, tumor suppressor genes including P53, BRCA1, 43 hMLH1, hMSH2, hMSH6, hPMS2 44,45 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that the bene t appears in all cancers and is not limited to any cancer in particular. For example, aspirin use has been associated with improved survival for colorectal cancer (HR = 0.38; 95% CI = 0.17-0.87; p = 0.02), 6 biliary tract cancer 7,8 , breast (adjusted HR=0.69, 95% CI 0.47-0.98), 9 prostate (adjusted hazard ratio, 0.43; 95% CI, 0.21 to 0.87; P = .02) 10 and Endometrial cancer (hazard ratio 0.46, 95% CI 0.25-0.86, P=.014). 11 Various mechanisms have been proposed to explain the protective role of aspirin in cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 85-88 We did not include tumor and/or pharmacogenomic alteration data in our analyses, but this should be a future consideration, exemplified by patients with wild-type PIK3CA, Lynch syndrome and KRAS-mutated colorectal cancers experiencing survival benefit from aspirin. 54 , 89 , 90 …”
Section: Discussionmentioning
confidence: 99%